2022
DOI: 10.1177/03635465221107364
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Safety and Effectiveness of Adipose-Derived Stromal Cell vs Stromal Vascular Fraction Injection for Treatment of Knee Osteoarthritis: 2-Year Results of Parallel Single-Arm Trials

Abstract: Background: There are currently no disease-modifying treatments available for knee osteoarthritis (OA), although cultured adipose-derived stromal cells (ASCs) have shown promise in experimental models. However, given the regulatory limits on the use of cultured cells in humans, previous trials have focused primarily on the stromal vascular fraction (SVF) intra-articular injection. Therefore, the therapeutic value of ASCs for knee OA remains unknown. Purpose: To study ASC versus SVF intra-articular injection in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…Meanwhile, recent studies inferred that the treatment was more effective in patients with K-L grade 3 than others. 1,47,52 In this regard, to avoid possible bias concerning the degree of osteoarthritis, the study included only knees with K-L grade 3 to evaluate the clear potency of the IA injection of ADMSCs because the degree of osteoarthritis reflects the severity of inflammation and destruction of the knee joint, which would affect the ADMSC efficacy. 1,47 A linear mixed model was used to detect differences between the groups during 24 weeks and included patients as a random effect and treatment groups, visit, and visit 3 treatment interaction as fixed effects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, recent studies inferred that the treatment was more effective in patients with K-L grade 3 than others. 1,47,52 In this regard, to avoid possible bias concerning the degree of osteoarthritis, the study included only knees with K-L grade 3 to evaluate the clear potency of the IA injection of ADMSCs because the degree of osteoarthritis reflects the severity of inflammation and destruction of the knee joint, which would affect the ADMSC efficacy. 1,47 A linear mixed model was used to detect differences between the groups during 24 weeks and included patients as a random effect and treatment groups, visit, and visit 3 treatment interaction as fixed effects.…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous literature, the MCID of the 100-mm VAS was set at 14 points and 20% relative improvement, and the MCID of the total WOMAC was set at 9 points and 33% relative improvement. 17,41,48,52…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such cells may be injected as single-cell preparations or as tissue-engineered constructs (reviewed in [ 4 , 28 ]). Single-cell injections have not proven to be very effective in repairing damaged cartilage, but they have been effective in clinical trials to affect pain and disability [ 99 , 100 ]. However, effectiveness may be negatively influenced by the intra-articular environment, particularly the presence of inflammation [ 4 , 101 ], in spite of their possible immunomodulatory role [ 102 , 103 ].…”
Section: Implications From Subtyping For Conservative Treatment For K...mentioning
confidence: 99%
“…In another recent study [ 169 ], however, improvements in MR findings were reported in 53 knees of 47 patients who had grade 2 and 3 OA of the knee at the 12-month follow-up. At the 6 [ 170 ] to 12 month [ 171 ] follow-up, patients with good outcomes were confirmed by 2 [ 172 ] to 5 [ 173 ] year follow-up studies.…”
Section: Adipose Derived Stromal Vascular Fraction (Ad-svf)mentioning
confidence: 99%